1994
DOI: 10.1902/jop.1994.65.2.162
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface‐Free Energy on Supra‐ and Subgingival Plaque Microbiology. An In Vivo Study on Implants

Abstract: The influence of surface free energy on supra‐ and subgingival plaque microbiology was examined in 9 patients with functional fixed prostheses supported by endosseous titanium implants. Two abutments (trans‐mucosal part of the 2 stage implant) were replaced by either a new titanium abutment or a fluor‐ethylene‐propylene (FEP) coated abutment per subject. After 3 months of habitual oral hygiene, plaque samples were taken. Supragingival plaque was examined by means of differential phase‐contrast microscopy, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 21 publications
1
38
0
1
Order By: Relevance
“…Drake et al 24 showed that hydrophobic titanium surfaces were preferentially colonized by Streptococcus sanguis. In contrast, Quirynen et al 3 reported that the amount of bacterial adhesion decreased on a fluorethylenepropylene coated group, in which the surfaces were hydrophobic. The results of this study also showed that P.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Drake et al 24 showed that hydrophobic titanium surfaces were preferentially colonized by Streptococcus sanguis. In contrast, Quirynen et al 3 reported that the amount of bacterial adhesion decreased on a fluorethylenepropylene coated group, in which the surfaces were hydrophobic. The results of this study also showed that P.g.…”
Section: Discussionmentioning
confidence: 91%
“…1 Comparatively large amounts of bacterial adhesion and plaque formation on titanium implants have been reported under in vitro and in vivo tests, and the necessity for plaque control has been pointed out. [2][3][4][5][6] However, there are few reports on the relationship between bacterial adherence and the physicochemical nature of implant surfaces. Moreover, few experiments have been conducted with surface modification to inhibit the adherence of oral bacteria on titanium implants.…”
Section: Introductionmentioning
confidence: 99%
“…These results are confirmed by other investigators who state that increasing surface roughness not only increases plaque retention 23,24,28,36,44) but also leads to plaque adhering much more rapidly and in larger quantities 20,25) . Comparing all influencing factors, several studies concluded that surface roughness plays the most important role in initial bacterial adhesion and the influence of surface roughness exceeds the influence of surface free energy 23,29,30,34,37) . Carlen et al state that polishing procedures lead to an unfavorable surface with lower protein resistance that is thus more prone to accumulate biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports relate plaque formation to substratum hydrophobicity. Some previous studies conclude that dental plaque formation is greater on hydrophilic restorative materials such as porcelain and metals than on hydrophobic materials such as amalgams and resins 25,29,[33][34][35] . Contrary studies, however, report greater plaque formation on hydrophobic materials and significantly lower adhesion to ceramics than to composite resin surfaces of polymeric origin or amalgams [36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated, that after three months the exposed areas of low s.f.e. FEP coated abutments (transmucosal dental implants) displayed lower bacterial colonization and a lower plaque maturation as compared to bare titanium [43]. However, in the areas covered by the gingiva, where less mechanical shear forces are present, this effect was not apparent.…”
Section: Low Surface Free Energy Coatingsmentioning
confidence: 99%